Recognition of Double-Stranded RNA and Regulation of Interferon Pathway by Toll-Like Receptor 10 - Lee, Suki Man-Yan; Yip, Tsz-Fung; Yan, Sheng; Jin, Dong-Yan; Wei, Hong-Li; Guo, Rey-Ting; Peiris, Joseph Sriyal Malik (Frontiers in Immunology, 2018)
Toll-like receptor (TLR)-10 remains an orphan receptor without well characterized ligands or functions. Here we reveal that TLR10 is predominantly localized to endosomes and binds dsRNA in vitro at endosomal pH, suggesting that dsRNA is a ligand of TLR10. Recognition of dsRNA by TLR10 activates recruitment of myeloid differentiation primary response gene 88 (MyD88) for signal transduction and suppression of interferon regulatory factor (IRF)-7 dependent type I IFN production. We also demonstrate crosstalk between TLR10 and TLR3, as they compete with each other for dsRNA binding. Our results suggest for the first time that dsRNA is a ligand for TLR10 and propose novel dual functions of TLR10 in regulating IFN signaling: first recognition of dsRNA as a nucleotide sensing receptor and second sequestration of dsRNA from TLR3 to inhibit TLR3 signaling in response to dsRNA stimulation.